Distributed space-frequency block coding for a 2-antenna relay in downlink OFDM systems - Teodoro, Sara
In this paper we evaluate the coded and uncoded performance of a 2-antenna terminal relaying schem, for downlink OFDM based systems, using efficient space-frequency block coding protocols. We consider that the relay and the base station are equipped with 2 antennas and the user terminal has a single antenna. Two types of relay protocols are accounted for: Equalize-and-Forward and Decode-and-Forward. Signals expressions are derived and the bit error rates obtained for a pratical and preeminent scenario, with LTE parameters and using convolutional channel coding. The performance of the proposed relay-assited scheme is evaluated under realistic scenarios, considering typical pedestrian scenarios based on LTE specifications. Results are compared to those of other relay-assisted design approaches that have been recently proposed for the case of 1-antenna relay and the non-cooperative systems. For this comparison, we implement three propagation scenarios, with different SNR transmission conditions among links. Simulation results show that the availability of a bi-antenna array at the relay significantly improves the cooperative system performance, but improvements are highly dependent on the scenarios and relay protocol as well as of the cooperative second-hop quality.